Transitional Justice as a Path to Distributive Justice: A Jurisprudential and Legal Case for Land Restitution in Kenya (Strathmore Law Review, 2016)
Rawls’ theory of distributive justice may serve as a useful model in conceptualizing a model of the ideal political economy – one that seeks to keep inequalities that have come about as a result of natural accident to a minimum. Moreover, his principles of justice can be used correctively, to address institutional inequalities that have the effect of entrenching social dislocation. Kenya has, over the decades up until now, been riven by injustices relating to land. This has led to the development of a small cluster of landed elites while the majority of citizens are effectively denied land access rights. This is regardless of the fact that most of the land so acquired by the former was acquired irregularly and with disregard of bona fide title of the original occupants. The concept and process of transitional justice may be viewed as the vehicle toward attaining corrective justice and accountability for offences committed in times of national crisis as a restorative measure.